A New High Sensitivity System to Detect Instabilities During the Extrusion of Polymer Melts. Issue 11 (20th August 2015) - Naue, Ingo F. C.; Kádár, Roland; Wilhelm, Manfred
Abstract: This publication is concerned with the development of a novel high sensitivity instability detection die for a laboratory size extruder. The high sensitivity system consists of piezoelectric transducers placed along the die length to monitor local pressure fluctuations, having temporal and pressure resolution of up to Δ t ≈ 10 −3  s and Δ p ≈ 10 −5 bar, at a nominal pressure of 500 bar. The system is tested on short chain branched polyethylenes, namely on the detection and characterization of the sharkskin instability. It is shown that the determined instabilities are related to characteristic peaks in the corresponding in situ pressure Fourier‐transform spectra and that other peaks are caused by different, but defined, sources. The in situ results obtained are validated through optical image analysis of the instabilities. Abstract : A novel high sensitivity instability detection die for a laboratory size extruder is presented. The high sensitivity detection system consists of piezoelectric transducers placed along the die length to monitor local pressure fluctuations, having remarkable temporal and pressure resolutions. The system is tested on short chain branched polyethylenes, namely on the detection and characterization of the sharkskin instability.